Effect of H2 addition during PECVD on the moisture barrier property and environmental stability of H:SiNx film. Issue 12 (13th July 2021) - Kim, Jingyu; Jeong, Wooseok; Lee, Seunghee; Jeong, Sehun; Ko Park, Sang‐Hee
Abstract: A hydrogenated silicon nitride (H:SiN x ) film with enhanced moisture barrier property and environmental stability was developed using plasma‐enhanced chemical vapor deposition (PECVD) with the addition of H2 gas at 100°C. The moisture barrier property and film density of the 100‐nm‐thick H:SiN x film were ameliorated by increasing the H2 gas flow rate during PECVD. X‐ray photoelectron spectroscopy and Fourier‐transform infrared spectroscopy studies demonstrated that the improved performance was a result of an increase in the amount of Si–N bonds compared to hydrogen‐terminated bonds with an increase in the H2 gas flow rate. It is believed that H2 gas assisted the formation of aminosilane, which contributed to the condensation of silicon nitride by lowering the activation energy for radicalization reactions of silane and ammonia. After the 85°C/85% RH test, the optimized H:SiN x film maintained a water vapor transmission rate lower than 5 × 10 −5 g/m 2 /day owing to the suppression of oxidation. The optimized H:SiN x film was rarely oxidized owing to the decrease in hydrogen‐terminated bonds and increase in the film density. The results indicated that the introduction of H2 gas during the PECVD process strengthened the environmental stability of the H:SiN x film.